Impacto das mudanças climáticas na produtividade primária de ambientes aquáticos tropicais: um estudo em microcosmo - Moura, Meirielle Euripa Pádua de (2015)
The global circulation of reports of the IPCC (Intergovernmental Panel on Climate Change) predict that climate change will alter the frequency currently registered in precipitation and temperature in the Earth's future climate scenarios. Resulting in aquatic environments changes in biodiversity and limnological. So chlorophyll becomes a quick and safe way to investigate these possible changes. This study aims to evaluate the effect of frequency of rainfall, temperature and time, considering future scenarios of global climate change on the concentration of chlorophyll-a in a microcosm. For the experiment was obtained water from a reservoir eutrophic landscaped with flowering filamentous cyanobacteria (Geitlerinema amphibium) and distributed in 40 beakers (microcosm). The experiment was conducted for two weeks and were considered two variables: precipitation and temperature. The variable rainfall was subjected to four levels: (no precipitation, homogeneous precipitation, and two types of concentrated rainfall to the temperature, the beakers were subjected to two levels. Current climate temperature (22 ° C) and future (25 ° C), and .. repeated measures (three cycles of five days each) The difference between treatments was checked using a Variance Factorial Analysis test for repeated measures (ANOVA) The rainfall did not change significantly the concentrations of chlorophyll-a, (F = 1.198; P = 0.326), on the other hand the temperature promoted an increase in the concentration of chlorophyll-a (F = 10.343;. P = 0.002) Therefore, from such evidence is expected that in future scenarios of climate change, there will be an increase in productivity primary in eutrophic environments, from changes in temperature. As a result, increase the duration of the cyanobacterial bloom period. This phenomenon can compromise the integrity of natural environments and requires measures to prevent the release of nutrients into waterways, like the treatment of waste before reaching the water bodies.